Seedlings morphology of confectionery sunflower at different pH of water solution - Varga, Ivana, agronomka (Array, 2021)
In this study the confectionery sunflower seed was tested to germination at different pH media, from 3.5 to 8.5. The experiment was set up at room temperature (22°C) and at 24 h dark conditions for 10 days. The mean germination rate was 76%. The highest germination rate was 86% at pH 3.5, whereas the lowest was 68% at pH 5.5. The ANOVA resulted with very significant influence of pH on sunflower seedlings root, stem and total length (p<0.001). The total length of seedlings was the shortest at acid media (9.2 cm at 3.5) and the longest at alkaline media (12.5 cm at pH 8.5). Regression equitations showed that increment of stem or root length and total length have a positive trendline at all pH levels. It was found that the alkaline water solution has a positive influence on protein sunflower seedlings development, but it would be valuable to found how the seeds would germinate at the field conditions.